PENGARUH MANAGERIAL ABILITY, CAPITAL INTENSITY DAN KOMPENSASI RUGI FISKAL TERHADAP TAX AVOIDANCE - Dewi Cahya Santika Putri (2023)
This study aims to determine the effect of managerial ability, capital intensity and fiscal loss compensation on tax avoidance in mining companies listed on the Indonesia Stock Exchange for the period 2017 to 2021. This study is a quantitative study with secondary data consisting of 38 samples of companies collected using purposive sampling method. Data analysis technique in this study uses a regression model selection test, classical assumption test of panel data regression and hypothesis testing and is processed using software STATA version 14. The result showed that there was a negative effect between managerial ability on tax avoidance, but there was no influence between capital intensity and fiscal loss compensation on tax avoidance. As for the control variabel, there is a positive influence between profitability on tax avoidance